J147 Reduces tPA-Induced Brain Hemorrhage in Acute Experimental Stroke in Rats - Jin, Rong; Wang, Min; Zhong, Wei; Kissinger, Charles R.; Villafranca, J. Ernest; Li, Guohong (Frontiers in Neurology, 2022)
Background and Purpose- J147, a novel neurotrophic compound, was originally developed to treat ageing-associated neurological diseases. Based on the broad spectrum of cytoprotective effects exhibited by this compound, we investigated whether J147 has cerebroprotection for acute ischemic stroke and whether it can enhance the effectiveness of thrombolytic therapy with tissue plasminogen activator (tPA). Methods - Rats were subjected to transient occlusion of the middle cerebral artery (tMCAO) by insertion of an intraluminal suture or embolic middle cerebral artery occlusion (eMCAO), and treated intravenously with J147 alone or in combination with tPA. Results – We found that J147 treatment significantly reduced infarct volume when administered at 2 hours after stroke onset in tMCAO model, but had no effect in eMCAO without tPA. However, combination treatment with J147 plus tPA at 4 hours after stroke onset significantly reduced infarct volume and neurological deficits at 72 h after stroke compared with saline or tPA alone groups in the eMCAO model. Importantly, the combination treatment significantly reduced delayed tPA-associted brain hemorrhage and secondary microvascular thrombosis. These protective effects were associated with J147-mediated inhibition of matrix metalloproteinase-9 (MMP9), 15-Lipoxygenase-1 (15-LOX-1), and plasminogen activator inhibitor (PAI) expression in the ischemic hemispheres (premoninently in ischemic cerebral endothelium). Moremore, the combination treatment significantly reduced circulating platelet activation and platelet-leukocyte aggregation compared with saline or tPA alone groups at 24 hours after stroke, which might also contribute to reduced microvascular thrombosis and neuroinflammation (as demonstrated by reduced neutrophil brain infiltration and microglia activation). Conclusions- Our results demonstrate that J147 treatment alone exerts cerebral cytoprotective effects in a suture model of acute ischemic stroke, while in an embolic stroke model co-administration of J147 with tPA reduces delayed tPA-induced intracerebral hemorrhage and confers cerebroprotection. These findings suggest that J147-tPA combination therapy could be a promising approach to improving treatment of ischemic stroke.